Homological Algebra and Divergent Series - Gorbounov, V.; Schechtman, V. (Symmetry, Integrability and Geometry: Methods and Applications, 2009)
We study some features of infinite resolutions of Koszul algebras motivated by the developments in the string theory initiated by Berkovits.